FROM PLATE TO PALETTE: DIETARY PATTERNS AND THEIR ROLE IN MUCOSAL LESIONS AMONG NORTH INDIAN COMMUNITIES: A CROSS-SECTIONAL STUDY - Lal, Kavisha Kapoor (2024)
Introduction: The global oral health scenario, as per WHO 2022 report, states that 3.5 billion people are affected by oral diseases. Despite oral mucous membrane's susceptibility to various diseases, scant information exists on oral lesions. This study aims to assess the impact of dietary habits on oral mucosal lesions in the North Indian population. Material and Methods: A community based cross-sectional survey was conducted in a rural area, involving 405 participants. Oral health questionnaires and clinical examinations were utilized for data collection. Chi-square test and Multivariate regression model were used for analysis. Results: Lesser fruit intake was associated with high prevalence of candidiasis (30%). Sweets consumption was linked with ulcerations (44.4%) an abscess (44.4%) and 4 to 9 times increased risk of oral lesions whereas soft drinks were linked with leukoplakia and candidiasis in 30.8% participants. Tea/coffee consumption was linked to malignant lesions. Conclusion: Significant proportion had oral mucosal lesions, notably influenced by diet and habits. Tea/coffee intake linked to malignant lesions; sweets to ulcers; soft drinks to leukoplakia. Tobacco showed significant associations. Oral lesion distribution varied across oral cavity regions, emphasizing diverse etiologies.